IMPROVING STUDENTS’ READING COMPREHENSION BY USING MULTI PASS STRATEGY ON NARRATIVE TEXT AT TENTH GRADE OF SMK START UP DARA JINGGA - Riyadi Saputra (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2020)
Reading comprehension becomes a problem in learning English for the tenth-grade students of SMK Start-Up Dara Jingga since they have low achievement in reading comprehension. This research aims at improving students' skills in reading comprehension by using Multipass Strategy. It is conducted by using classroom action research which contains planning, action, observation, and reflection. Subjects of this research were students of the tenth-grade of SMK Start Up Data Jingga. The class consisted of 16 students; 7 boys and 9 girls. Then, the data of this research were quantitative and qualitative. The quantitative data were gained from scores of students of the reading task and test in every cycle. Meanwhile, the qualitative data were collected through the result of observation. The finding of the research from cycle 1 up to cycle 2 shows that Multiple Strategy enables to improve students’ skill in reading comprehension. In cycle 1, the students' score increases to 87.5 %. Furthermore, the increase of the quantitative data was supported by qualitative data, such as classroom activity, teaching, strategy, and teachers. It can be said that multipass strategy can be used to improve the students' skills in reading comprehension especially at tenth-grade students of SMK Start-Up Dara Jingga.